Influence of Geometry and Hardness of the Backing Plate on Ballistic Performance of Bi-Layer Ceramic Armor - Gour, Govind (2018)
The high hardness and strength of technical ceramics is exploited to design ballistic armors and their low toughness, brittleness is overcome by joining them with a metallic or long fiber reinforced composite backing plate. The thickness of backing plate (BP) on the ballistic performance SiC ceramic armor is studied through finite element simulations based on AUTODYN®. In this work, depth of penetration (DOP) from experimental measurements is compared with simulations using explicit software AUTODYN® for 3D modelling. The ballistic performance of three layer armor (cover plate (CP), ceramic tile and backing plate (BP)) under normal and oblique (NATO 60°) for long rod projectile (LRP) with a conical tip is investigated. The LRP and CP have been modelled using smooth particle hydrodynamic (SPH) particles and rest of the component is modelled using lagrangian processor. The Johnson-Cook and Johnson-Holmquist (JH-2) constitutive models are used for metal and ceramic materials, respectively. It is found that thicker BP enhances SiC armor via supporting longer period and prevent any premature failure at the rear surface of ceramic. It is also noticed that high hardness (low ductile) BP improves the ballistic performance of ceramic armor through offsetting tension of ceramic.